NIKEL LATERITIK DI DAERAH TANAH MERAH, TABLASUFA DAN ORMO, KABUPATEN JAYAPURA, PROPINSI PAPUA - -, Geni Dipatunggoro (Fakultas Teknik Geologi Universitas Padjadjaran, 2007)
Nickel occurs in bedrock of ultramafic spread surrounding Jayapura to the west along the northeren beach of Papua, Occurs in layers of soil called Limonit and Saprolit where both are weathered of ultramafic bedrocks includes Peridotit, Harsburgit, Serpentinit, Dunit and Lerzolit.The geology of Jayapura including distribution of ultramafic and metamorphic rocks of Pra-Tersier age was uplifted to the land since the tectonic of Early Miocene to the present was subjected to some active tectonic characterized by steep and sharp morphology.From the result of previous investigations indicates that nickel grade are excellent and being prospective for industrial word especially in China. The highest obtained nickel grade reached 6 %.Fild investigation show the occurrence of DMP (Associated Minerals) in nickel area e.g. Iron (Fe), Cobalt (Co) and Chrom (Cr).